PENGEMBANGAN MODUL BERBASIS REALISTIK PADA MATERI PERBANDINGAN DALAM PEMBELAJARAN MATEMATIKA KELAS VII SMPN 35 PADANG - Rostari, Riren - (Pendidikan Matematika, 2014)
The background of the research is the need of teaching material in the learningprocess. The expected teaching material is the teaching material that proposes thereal problem in the beginning of the learning involving the students in buildingconcepts so that it will facilitate the students to study independently. The schooltextbook has not proposed the real problem in the beginning of the learning andfacilitated the students to study independently. Therefore, it is made a teachingmaterial in the form of a realistic-based module of comparison material. Theresearch aims to know the validity and practice of module. The type of theresearch is the development of ADDIE model. ADDIE model consists of Analysis,Design, Development, Implementation, and Evaluation. The validity test resultshows that the module of very valid criteria is 88.26%. Meanwhile, the teacherpractical test result shows that the module of very practical criteria is 97.77% andthe student practical test result shows that the module of very practical criteria is98,33%. It can be concluded that the realistic-based module is valid and practical.